Couple resilience predicted marital satisfaction but not well-being and health for married couples in Bali, Indonesia - Surijah, Edwin Adrianta; Prasad, Gaura Hari; Saraswati, Made Rinda Ayu (Psikohumaniora: Jurnal Penelitian Psikologi, 2021)
Married couples face various challenges in their married life, with divorce being one of the threats to their relationship. Spouse resilience is the process by which couples manage marital challenges through positive relationship behavior. This study examines the resilience of partners by including negative behavior in the relationships and examines the effects of interactions between partners. Three hundred couples living in Bali, Indonesia (length of marriage of between 1-10 years) participated by reporting positive and negative behaviors, and the outcomes of their relationship (marital satisfaction, emotional well-being, and general health status). The measurement instruments employed were the Couple Resilience Inventory, Satisfaction with Married Life Scale, and the 36-item Short-Form Health Survey. Model fit analysis showed that behavior in relationships did not predict the outcomes referred to above, and that there was no interaction effect between partners. However, positive behavior showed a higher probability of predicting marital satisfaction, especially for wives (β = .271; β = .403; p < .001). The implications of these findings provide practical suggestions for future partner resilience research to apply a longitudinal approach that repeatedly measures the outcomes of resilience.